THE THINK PAIR SHARE TYPE OF COOPERATIVE LEARNING MODEL APPLICATION USING SCIENTIFIC APPROACH WITH VIDEOSCRIBE MEDIA AID TO IMPROVE LEARNING ACTIVENESS OUTCOME OF THE 10TH GRADERS OF SMA N 3 SUKOHARJO - Arini, Narita Dyah (International Journal of Active Learning, 2019)
The objective of research was to find out whether or not the use of Think Pair Share model with scientific approach with videoscribe aid can improve learning activity and outcome of students.This study was a classroom action research. The subject of research was the 10th Social Science 1 (X IPS 1) graders consisting of 35 students, and X IPS 4 graders consisting of 36 students in SMA Negeri 3 Sukoharjo. Techniques of collecting data used were observation, interview, documentation, and questionnaire. Techniques of analyzing data used in this study was qualitative and quantitative data analyses, while the combination method employed was convergent parallel mixed methods in which the author collects quantitative and qualitative data at the same time, analyzes the data separately, and compares the result to find out whether or not the findings are overlapping.The result of research showed that the application of Think Pair Share using scientific approach with videoscribe aid in Economics subject could improve learning activeness and learning outcome in the 10th Social Science 1 and 10th Social Science 4 graders in SMA Negeri 3 Sukoharjo. It was characterized with the increase in learning activeness in the X IPS 1 graders of SMA Negeri 3 Sukoharjo from 66.84% prior action to 81.29% in cycle I and 81.29% in cycle II. It was followed with the increase in learning outcome of X IPS 1 graders of SMA Negeri 3 Sukoharjo from 33.33% of students passing successfully the MMC prior action to 68.57% in cycle I and to 88.57% in cycle II. The increase of learning motivation also occurred in X IPS 4 grade of SMA Negeri Sukoharjo following the application of Think Pair Share model using scientific approach with videoscribe aid from 63.93% prior action to 70.20% in cycle I and to 81.48% in cycle II. It was followed with the improvement of students’ learning outcome from 13.88% of students passing successfully the MMC prior action to 75% of students doing so in cycle I and 91.67% of students in cycle II.